2005
DOI: 10.1016/j.jvs.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Graft-associated hemorrhage from femoropopliteal vein grafts

Abstract: GAH is a serious complication with high morbidity, mortality, and transfusion requirements. Although technical problems are preventable, FPV grafts, like all biologic grafts, can develop disruption with GAH from ongoing infection, especially in severely immunocompromised patients who are malnourished and have poor healing ability. Strategies for prevention and alternative treatment modalities are appropriate in patients at high risk for GAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…We have previously reported that graft disruption of FPV grafts occurs in the setting of ongoing contamination of the graft, severe malnutrition, immunosuppression and debilitated state. 25 In the 10 patients with disruption, six had AE fistula or erosion. Five of these six patients had had persistent leakage of enteric contents that was contiguous with FPV grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that graft disruption of FPV grafts occurs in the setting of ongoing contamination of the graft, severe malnutrition, immunosuppression and debilitated state. 25 In the 10 patients with disruption, six had AE fistula or erosion. Five of these six patients had had persistent leakage of enteric contents that was contiguous with FPV grafts.…”
Section: Discussionmentioning
confidence: 99%
“…These have been previously reported. 25 Most of the graft disruptions occurred within the first 2 weeks after NAIS. We attribute this to reinfection but this was documented in only a few of these patients.…”
Section: Demographicsmentioning
confidence: 99%
“…Even in the most experienced hands it has led to unfortunate incidences of graft-related hemorrhage from a popped tie. 16 Thus, it is paramount that the vein harvest is done in a safe and unhurried manner. The vein harvest can take anywhere from 2 to 3 hours, or even longer when performed by a surgeon not familiar with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While infection rates for autologous venous and arterial grafts is low, there is a substantial increase of infections in synthetic grafts with devastating complications including sepsis, anastomotic disruption with mass haemorrhage and pseudoaneurysm formation, graft thrombosis limb loss and high perioperative and late mortality [171], [172]. Infra-inguinal arterial prosthetic graft is associated with substantial early mortality and amputation rates [173].…”
Section: Infections Of Other Implantable Medical Devicesmentioning
confidence: 99%